Coming to terms : the rhetoric of narrative in fiction and film - Chatman, Seymour Benjamin (Ithaca, N.Y. : Cornell University Press, 1990)
TABLE OF CONTENTS##- Narrative and two other text-types##- Description is no textual handmaiden##- What is description in the cinema?##- Argumentation in film: Mon oncle d'Amérique##- In defense of the implied author##- The implied author at work##- The literary narrator##- The cinematic narrator##- A new point of view on "point of view"##- A new kind of film adaptation: The French lieutenant's woman##- The "rhetoric" "of" "fiction."
Includes bibliographical references (p. 205-234) and index.
boek